Relationships between perceived stress, parental attachment, peer attachment, religiosity-spirituality, and life satisfaction among Malaysian undergraduates in private universities - Rahmat, Hawa (2018)
A growing body of literature has shown significant impacts of life satisfaction on health and longevity, psychological, social and educational functioning at all level of developmental stages. Research on life satisfaction is particularly important among undergraduates because they are continuously faced with stress in campus such as academic challenges, personal issues, relationship concerns, and at the same time have to fit in with social activities in campus, which in turn affect their life satisfaction. It is specifically critical to study life satisfaction of undergraduates in the private universities because private and public universities are different in mission and vision, and the ways in running the business. Not only they imposed higher fees, private universities are also considered as “second chances” places for those who failed to study in public universities, having inadequate facilities, offered limited courses and English as the medium of instruction could influence students’ moral and social life, in turn affect their life satisfaction. However, with scarce studies on life satisfaction among Malaysian sample, it is deemed essential to study on factors directly and indirectly associated with life satisfaction among Malaysian undergraduates. The present study examines the relationships between perceived stress, paternal attachment, maternal attachment, peer attachment, religiosity-spirituality, and life satisfaction among undergraduates in Malaysian private universities. Gender is manipulated in order to examine the differences in life satisfaction between male and female undergraduates. The study also seeks to determine the unique predictors of life satisfaction among the undergraduates. Peer attachment is examined as a mediator between perceived stress, paternal attachment, maternal attachment and life satisfaction. Religiosity-spirituality is also examined as a moderator on the relationships between perceived stress and life satisfaction among the respondents. In total, 400 students from four selected private universities in Malaysia participated in the study. The instruments used were Satisfaction with Life Scale (SWLS) (Diener et. al, 1985), Inventory of College Students’ Recent Life Experiences (ICSRLE) (Kohn et. al, 1991), Inventory of Parent and Peer Attachment (IPPA) (Greenberg and Armsden, 1987), and Brief Multidimensional Measurement of Religiousness- Spirituality (BMMRS) (Fetzer Insitute, 2003). Random sampling was used to gather data from the respondents in the class. The SEM-AMOS was generated to examine the model based on the integrations of Top-down Theory and Attachment Theory as the theoretical framework of the study. The model has met all the three required fitness indexes; the RMSEA (0.069), Chisq/df (2.920), and CFI (0.938). Perceived stress maternal attachment, paternal attachment, and peer attachment significantly correlated with life satisfaction. The study does not significantly show any difference between male and female in the young adult’s life satisfaction. The standardized beta coefficients for perceived stress do not equal zero when regressed against undergraduates’ life satisfaction. It indicates that perceived stress is stronger predictor of life satisfaction relative to other independent variables. Parental attachment appears to be second main predictor of life satisfaction after perceived stress. However, peer attachments do not significantly mediate the relationships between perceived stress, parental attachment, and life satisfaction. Meanwhile, religiosity-spirituality was significantly moderate the relationships between perceived stress and life satisfaction among the undergraduates. In conclusion, the study highlights significant association of perceived stress, maternal attachment, paternal attachment, peer attachment, and life satisfaction. The study also revealed positive roles of religiosity-spirituality in moderating the relationship between perceived stress and life satisfaction among young adults studying in the universities. The findings add valuable input on the existing body of knowledge in the field of developmental psychology specifically on the study between perceived stress, parental attachment, peers attachment, religiosity-spirituality, and life satisfaction among undergraduates.